2016
DOI: 10.1021/acs.analchem.6b00982
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA Methylation of G-Quadruplex and i-Motif-Forming Sequences by Measuring the Initial Elongation Efficiency of Polymerase Chain Reaction

Abstract: DNA methylation has been proposed as one of the promising biomarkers for cancer diagnosis. In this study, we developed a DNA methylation detection system utilizing G-quadruplex and i-motif-forming sequences that requires neither sodium bisulfite treatment nor methylated DNA ligands. We hypothesized that G-quadruplex and i-motif structures would be stabilized by DNA methylation and arrest DNA polymerase activity during quantitative polymerase chain reaction (qPCR). The PCR products from VEGF, RET G-quadruplex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…The formation of i‐motif structures can lead to arrest of cellular processes that require transient opening of the double helix, such as transcription and DNA replication . To determine the effect of i‐motif structures in ACC1 promoters on DNA replication, a polymerase stop assay was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of i‐motif structures can lead to arrest of cellular processes that require transient opening of the double helix, such as transcription and DNA replication . To determine the effect of i‐motif structures in ACC1 promoters on DNA replication, a polymerase stop assay was performed.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the Bcl-2 G4 structure and quadruplex structure of C9orf72 repeat were stabilised by DNA methylation 36 , 37 . We reported that the initial elongation efficiency of PCR decreased with increasing DNA methylation levels in VEGFA and RET G4-forming sequences 38 , indicating that the G4 structures are also stabilised by DNA methylation. These reports suggest that our method could be applied to detect epigenetic modification by identifying G4 clusters stabilised by DNA methylation.…”
Section: Discussionmentioning
confidence: 89%
“…Given the exclusivity of 5-mC with both iM/G4-forming regions and with 5-hmC, the overall purpose of this study was to examine the effects of 5-hmC modification on the formation, stability, and recognition of secondary DNA structures. As a physiologically relevant model, we focused on the structures in the promoter of the VEGF gene, which have been well-described for both iM and G4 formation [ 12 , 14 , 29 31 ] and containing natural CpG islands [ 40 ]. Cytosine modification of this promoter has been shown to vary with pathophysiological states [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%